Information security policies compliance in a global setting: An employee's perspective. Issue 129 (June 2023) - Alraja, Mansour Naser; Butt, Usman Javed; Abbod, Maysam
Abstract: Information security threats have a severe negative impact on enterprises. Organizations rely on employee compliance with information security policies to eliminate or reduce these hazards. The Unified Model of Information Security Policies Compliance (UMISPC) is employed to identify the factors that may affect employees' intention towards compliance with information systems security policy and reactance in a global setting. The study was assessed in two phases. The model's validity and measurement reliability were evaluated in the first phase, while in the second phase, all preliminary model relationships were appraised. This was achieved utilizing structural equation modelling to establish whether the proposed constructs, i.e. neutralization, response efficacy, fear, threat, habit and role values were good predictors for intention or reactance towards compliance with information systems security policy. Participants included 348 employees from 7 nations, i.e. the USA, the UK, Oman, India, Pakistan, Malaysia, and the Philippines. SmartPLS v. 3.3.9 was used for data analysis. The models' measurement reliability and validity were affirmed. Fear and role values have a significant influence on intention toward ISPC. RE significantly predicted threat which in turn significantly predicted fear, and the latter demonstrated a significant effect on reactance as well as Neutralization predicted reactance. In contrast, habit failed to reach a significant influence on intention towards ISPC. The implications are presented, together with proposals for further studies. Our findings are helpful for ISS literature and application by supporting the crucial functions of role values in encouraging employees to behave in a compliant manner. Additionally, it is regarded as the first empirical attempt to estimate intended compliance concerning ISPs in higher education from a worldwide viewpoint.